1994
DOI: 10.1007/bf00185077
|View full text |Cite
|
Sign up to set email alerts
|

Lung surfactant components in bronchoalveolar lavage after inhalation of NO2 as markers of altered surfactant metabolism

Abstract: To study the effects of nitrogen dioxide (NO2) inhalation on lung lavage surfactant components as markers of an altered surfactant metabolism in type II pneumocytes, rats were exposed to atmospheres with increasing NO2 concentrations (0.8, 5.0, and 10.0 ppm) over 1 and 3 days. After exposure lung lavage was performed and surfactant components as well as lavageable cells analyzed. An increased number of total lavage cells was found with increasing concentration and duration of NO2 exposure. Cell distribution sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The amount of saturated PC was decreased, and the amount of unsaturated PC was increased. These investigators also observed an impaired surfactant function [89]. Lower PC levels may be caused by a decreased production and secretion of disaturated PC as observed in rats exposed to 5 ppm NO 2 for 48 h [81].…”
Section: Nitrogen Dioxidementioning
confidence: 74%
“…The amount of saturated PC was decreased, and the amount of unsaturated PC was increased. These investigators also observed an impaired surfactant function [89]. Lower PC levels may be caused by a decreased production and secretion of disaturated PC as observed in rats exposed to 5 ppm NO 2 for 48 h [81].…”
Section: Nitrogen Dioxidementioning
confidence: 74%
“…Finally, NO 2 concentrations of 1.5 ppm increased granulocyte and macrophage recruitment in the lungs [25] and produced hypertrophy of alveolar septa after 6 weeks of NO 2 exposure [26]. Conversely, no significant alterations in the number of inflammatory cells, in phospholipid content and in functional properties of surfactant could be demonstrated after NO 2 exposures of 0.8 ppm for 3 days in lung lavage products from rat lungs [27]. In our study, no evidence of pulmonary inflammation or acute distal injury due to 20 ppm NO inhalation could be found.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, in a model of acute lung injury from sepsis and hyperoxia, there was no difference in total surfactant levels or large aggregates in lavages between wild and inducible NOS (Ϫ/Ϫ) knockout mice (4). The conflicting results between in vivo and in vitro studies may be explained by the presence of various antioxidants within epithelial lining fluid in vivo not present in vitro, which inactivates the toxic intermediates of NO, such as peroxynitrite (26,27,29,43,60), methemoglobin (30,31,33), and nitrogen dioxide (45), which affect SP synthesis, secretion, or function.…”
Section: Discussionmentioning
confidence: 99%